2019
DOI: 10.1002/pro.3630
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing proteins in their cellular environment: Examples of recent advances in quantitative fluorescence microscopy

Abstract: Quantitative characterization of protein interactions, both intramolecular and intermolecular, is crucial in understanding the mechanisms and regulation of their function. In recent years, it has become possible to obtain such information on protein systems in live cells, from bacteria to mammalian cell lines. This review discusses recent advances in measuring protein folding, absolute concentration, oligomerization, diffusion, transport, and organization at super-resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The original molecular switch model of NR function assumed that NRs were bound to their response elements on the DNA statically and only the cofactors were exchanged in response to ligand binding. Biophysical experiments have shown that NRs were more dynamic and performed diffusive motion with different mobilities ( 6 , 8 , 9 , 10 , 12 , 13 , 14 , 33 ). Previously we demonstrated that agonist binding enhanced the DNA binding of RAR and RXR in a coactivator-dependent manner ( 6 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original molecular switch model of NR function assumed that NRs were bound to their response elements on the DNA statically and only the cofactors were exchanged in response to ligand binding. Biophysical experiments have shown that NRs were more dynamic and performed diffusive motion with different mobilities ( 6 , 8 , 9 , 10 , 12 , 13 , 14 , 33 ). Previously we demonstrated that agonist binding enhanced the DNA binding of RAR and RXR in a coactivator-dependent manner ( 6 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the help of modern quantitative microscopy techniques, we and others were able to decipher molecular details of the mechanism of action of transcription factors in single live cells. With such methods, the dynamic properties of interacting molecular subpopulations and proximities within molecular complexes could be dissected ( 6 , 11 , 12 , 13 , 14 , 25 , 33 , 40 , 41 , 42 ). Previously, we have already confirmed the heterodimerization of RAR and RXR by demonstrating their molecular proximity and comobility using SPIM-FRET-FCCS ( 7 ).…”
Section: Discussionmentioning
confidence: 99%